1995
DOI: 10.1111/j.1365-3024.1995.tb01000.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the site of parasite inoculation on the development of Th1 and Th2 type immune responses in (BALB/c × C57BL/6) F1 mice infected with Leishmania major

Abstract: Although inbred strains of mice are classified as genetically resistant or susceptible to Leishmania major based upon their ability to control infection, other factors such as the strain, dose, and site of parasite inoculation can also affect the outcome of the disease. Here we used the F1 progeny of BALB/c (susceptible) and C57BL/6 (resistant) mice (designated CB6F1) to investigate whether mice or intermediate susceptibility to infection differed from the parental strains in their ability to control infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 27 publications
2
47
1
Order By: Relevance
“…Why nonionic surfactant vesicles were unsuccessful as an adjuvant for NSO to induce a type 1 immune response in the current study was not determined. Previous studies have shown that the use of high doses of antigen and the subcutaneous inoculation route, as carried out in the current study, can result in a bias toward disease-enhancing type 2 responses (13,17,26), regardless of the adjuvant used. A similar phenomenon could be occurring in N. caninum immunizations.…”
Section: Discussionmentioning
confidence: 64%
“…Why nonionic surfactant vesicles were unsuccessful as an adjuvant for NSO to induce a type 1 immune response in the current study was not determined. Previous studies have shown that the use of high doses of antigen and the subcutaneous inoculation route, as carried out in the current study, can result in a bias toward disease-enhancing type 2 responses (13,17,26), regardless of the adjuvant used. A similar phenomenon could be occurring in N. caninum immunizations.…”
Section: Discussionmentioning
confidence: 64%
“…Prior studies have suggested that the site of primary infection can influence the outcome of disease and the Th1/Th2 balance of the primary immune response (3,9,26,27). In addition, Kirkpatrick et al have shown that the site of primary infection involving different intradermal sites on the back can influence the severity of the primary lesion and the resolution of a secondary lesion following reexposure to L. major (18).…”
Section: Discussionmentioning
confidence: 99%
“…Leishmania-specific Ab was determined by ELISA based on a previously described assay (23). Briefly, polystyrene microtiter plates (Dynatech Laboratories) were coated with 1.0 g of L. major Ag (SLA) per ml in PBS (pH 7.4) overnight at 4°C.…”
Section: Igg1 and Igg2a Ab Titersmentioning
confidence: 99%